A plasmon-tuned 'gold sandwich' for metal enhanced fluorescence in silica coated NaYF4:Yb, Er upconversion nanoparticles. Issue 90 (13th September 2016) - Manurung, Robeth Viktoria; Wu, Chien Ting; Roy, Pradip Kumar; Chattopadhyay, Surojit
Abstract : Upconversion nanoparticles, with a silica shell, demonstrate ∼20× metal enhanced fluorescence when sandwiched between a thick bottom layer, reflecting the 980 nm back to the UCNPs, and a thin top layer, creating a plasmonic field at 550 nm, of gold. Abstract : The low quantum yield of luminescence from lanthanide-doped up-conversion nanoparticles (UCNPs) has been enhanced by using an optimized 'gold sandwich' with a transparent top layer and a reflecting bottom layer at 980 nm excitation. Erbium (Er)-doped UCNPs, with a NaYF4:Yb, Er core, were synthesized by a thermal decomposition process and coated with silica to assist in metal-enhanced fluorescence (MEF). A bottom layer of thick coalesced gold island film, acting as a mirror, increases the optical path length of the 980 nm radiation through the UCNP layer dispersed on it. This layer enhances the UCNPs' 540 nm green emission by a factor of 5–8 compared to that in the absence of the gold reflector. A thin nanoparticle-like gold layer on top of the UCNPs, with a surface plasmon absorption around ∼550 nm, completes the sandwich, which augments the luminescence enhancement by another factor of ∼2.5, thus taking the net enhancement factor to ∼13–19 when compared to the luminescence in the absence of the gold-sandwich. The surface plasmon absorption in the top gold layer enhances the local electric field at the UCNPs to promote their radiative decay. Compared to previous reports, mostly for the solution state, the current case study is a solid state measurement.